Memories of my melancholy whores - García Márquez, Gabriel, 1927-2014 (Vintage International, 2006)
"Memories of My Melancholy Whores is Gabriel García Márquez's first work of fiction in ten years, written at the height of his powers, the Spanish edition of which Ilan Stavans called, 'Masterful. Erotic. As hypnotizing as it is disturbing' (Los Angeles Times). On the eve of his ninetieth birthday, our unnamed protagonist-an undistinguished journalist and lifelong bachelor-decides to give himself 'the gift of a night of wild love with an adolescent virgin.' The virgin, whom an old madam procures for him, is splendidly young, with the silent power of a sleeping beauty. The night of love blossoms into a transforming year. It is a year in which he relives, in a rush of memories, his lifetime of (paid-for) sexual adventures and experiences a revelation that brings him to the edge of dying-not of old age, but, at long last, of uncorrupted love. Memories of My Melancholy Whores is a brilliant gem by the master storyteller"--Publisher description.